2005
DOI: 10.1385/ijgc:35:1:025
|View full text |Cite
|
Sign up to set email alerts
|

p27<SUP>kip1</SUP> Expression Is Inversely Related to the Grade of Gastric MALT Lymphoma

Abstract: p27kip1 may be a putative distinct molecular marker to differentiate between low-grade and high-grade gastric lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…Our results confirm a strong correlation between the presence of H. pylori in gastric adenocarcinoma and a lack of p27 expression as 37 out of 42 samples with positive ureA were negative for p27 expression with a significant association (p = 0.001). This result is consistent with a study done in vitro by Shirin et al, who found a strong correlation between the presence of H. pylori and the inhibition of p27 immunoexpression [46]. Although prior studies have indeed found a correlation between different carcinoma types and expression of p27, we believe this is the first study to document this using validated viable gastrectomy samples.…”
Section: Discussionsupporting
confidence: 92%
“…Our results confirm a strong correlation between the presence of H. pylori in gastric adenocarcinoma and a lack of p27 expression as 37 out of 42 samples with positive ureA were negative for p27 expression with a significant association (p = 0.001). This result is consistent with a study done in vitro by Shirin et al, who found a strong correlation between the presence of H. pylori and the inhibition of p27 immunoexpression [46]. Although prior studies have indeed found a correlation between different carcinoma types and expression of p27, we believe this is the first study to document this using validated viable gastrectomy samples.…”
Section: Discussionsupporting
confidence: 92%
“…Our results confirm a strong correlation between the presence of H. pylori in gastric adenocarcinoma and a lack of p27 expression as 37 out of 42 samples with positive ureA were negative for p27 expression with a significant association (p = 0.001). This result is consistent with a study done in vitro by Shirin et al, who found a strong correlation between the presence of H. pylori and the inhibition of p27 immunoexpression [63]. Although prior studies have found a correlation between different carcinoma types and expression of p27, we believe this is the first study to document this using validated viable gastrectomy samples.…”
Section: Discussionsupporting
confidence: 92%
“…Kip1 expression in gastric MALT lymphomas and DLBCLs correlated with the grade of the lymphoma, irrespective of the stage 13 . While p27 Kip1 was not detectable in either the large cell or MALT components of DLBCLs with MALT lymphoma, p27…”
Section: Discussionmentioning
confidence: 88%